Stability of an Innovative Cold-Formed GEB Section - ŁUKOWICZ, Agnieszka; KRAJEWSKI, Marcin (Engineering Transactions, 2017)
This paper is focused on the numerical analysis and experimental test of stability of the cold-formed profile with an innovative GEB cross-section. For the shell model of the axially compressed member, the linear buckling analysis and the nonlinear static analysis were carried out. In the numerical research, the buckling load and the limit load for variable section heights were obtained. Some of the results were compared with the GEB member bearing capacity calculated on the basis of PN-EN 1993-1-1 Eurocode 3 requirements.